Spanish translation and validation of a brief measure of anxiety by the COVID-19 in students of health sciences - Caycho-Rodríguez, Tomás (2020)
Introduction and objectives: COVID-19 has generated negative consequences for people's mental health. This is the case of Peru, one of the Latin American countries most affected by the pandemic. In this sense, the objective of the study was to translate and validate the Coronavirus Anxiety Scale (CAS) into Spanish. Material and method: The participants were 704 university students of health sciences (Mage = 23.39 years, SD = 3.45) who were administered the CAS in Spanish, the Mental Health Inventory-5 and the Patient Health Questionnaire-2 item. The CAS was translated into Spanish using the forward and backward method. Reliability and evidence of validity based on internal structure and relationship with other variables were examined. Results: The factor analysis confirmed the one-dimensional factor structure of the CAS (χ2 = 7.62, df = 5, p = .18, χ2 / gl = 1.52, CFI = .99, RMSEA = .03 [90% CI. 00,. 06]; SRMR = .02, WRMR = .52); In addition, the factor loadings were large and significant (from. 68 to. 87). The five CAS items showed acceptable corrected total test item correlations (from. 64 to. 74). Reliability due to internal consistency was good (ω = .89; αordinal = .89). The validity evidence based on the relationship with other CAS variables was supported by the positive correlation with depression (r = .52, p < .01) and negative with subjective well-being (r = -.50, p < .01). Furthermore, depression mediates the relationship between COVID-19 anxiety and subjective well-being (bootstrap value = -. 24, 95% CI = -. 28, -. 20). Conclusion: The Spanish version of the CAS has evidence of validity and reliability to measure anxiety by COVID-19 in a sample of Peruvian university students.